2007
DOI: 10.1001/archsurg.142.7.624
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Prevalence and Severity of Clostridium difficile Colitis in Hospitalized Patients in the United States

Abstract: To evaluate changes in the epidemiological features of Clostridium difficile colitis in hospitalized patients in the United States (C difficile is a common cause of nosocomial diarrhea that has been shown to be increasing in virulence in Canada and across Europe).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
168
3
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(183 citation statements)
references
References 28 publications
8
168
3
4
Order By: Relevance
“…Diagnostic codes from the International Classification of Diseases (ICD-9) were used to identify all patients who were discharged with a diagnosis of C. difficile-pseudomembranous colitis (ICD-9 code 8.45) [1,2] from January 2000 to December 2003. Patients with either a primary or secondary diagnosis of CDAD were summed to calculate yearly hospital rates/1000 discharges.…”
Section: Hospital Infection Ratesmentioning
confidence: 99%
See 2 more Smart Citations
“…Diagnostic codes from the International Classification of Diseases (ICD-9) were used to identify all patients who were discharged with a diagnosis of C. difficile-pseudomembranous colitis (ICD-9 code 8.45) [1,2] from January 2000 to December 2003. Patients with either a primary or secondary diagnosis of CDAD were summed to calculate yearly hospital rates/1000 discharges.…”
Section: Hospital Infection Ratesmentioning
confidence: 99%
“…Clostridium difficile-associated disease (CDAD) is a common cause of nosocomial diarrhoea and is associated with substantial morbidity and mortality [1]. Recent population-based data reveal an increase in the prevalence and severity of CDAD in the United States [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These rates are lower than those reported for developed countries (4,31). Despite differences in geographic area and culture in these countries, inaccurate results could be obtained due to the need for individual equipment and defined culture media for the detection of these pathogens in patients' stool samples.…”
Section: Discussionmentioning
confidence: 70%
“…In the past two decades, epidemiological data derived from US national administrative databases, hospital-based reports and populationbased studies have shown a two to four fold increase in the incidence of CDI in the past two decades, especially in the elderly [Ricciardi et al 2007;Zilberberg et al 2008aZilberberg et al , 2008b; [Muto et al 2005;McDonald et al 2006]. An outbreak in Quebec reported in 2004 showed increasing severity and a high mortality rate of 6.9% [Pepin et al 2004].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%